Personality traits as drivers of social preferences: a mixed logit model application - Friederike Paetz (Journal of Business Economics, 2020)
Currently, social consumption constitutes a rapidly increasing trend with significant potential for companies; moreover, the characterization of social consumers is highly relevant. To date, sociodemographic variables have been widely studied but appear to be less appropriate to uniquely characterize social consumers. Psychographic variables are credited with the ability to overcome these problems, since recent studies maintain that consumers' personal values and lifestyles are predictors of social consumption. However, personal values and lifestyle represent only two categories of psychological variables. Personality is another variable further known to be an antecedent of personal values and lifestyle. In this study, we focus on the characterization of social consumers based on both their personalities and sociodemographic variables. We conduct an empirical discrete choice experiment and investigate consumers' personalities as a driver of consumer preferences for the fair trade (FT) label attribute. To operationalize consumers' personalities, we use the popular five-factor approach. For the determination of consumers' preferences, we estimate a mixed logit model including both unobserved preference heterogeneity and observed heterogeneity. Observed heterogeneity is captured by consumers' personalities and sociodemographic variables. We find that gender, academic degree, income and four personality traits are important drivers of consumers' social preferences. We determine the interaction effects between sociodemographic and personality variables and argue for the consideration of personality in the characterization of social consumers as the core source of social preferences. A subsequent simulation study provides further insight into marketing strategies derived from the personality-characterization of social consumers.
Keywords: M31-C38; 650; Discrete choice experiment; Heterogeneity; Social product preference; Consumer personality